2017
DOI: 10.1016/j.adolescence.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioural predictors of adolescents' communicative perspective‐taking and social relationships

Abstract: Given the pivotal role that social interactions play for adolescents' well-being, understanding the factors that influence communication is key. The present study examined relations between adolescents' communicative perspective-taking, executive function skills, and ADHD traits and explored the role communicative perspective-taking plays in peer relations. Data was collected from a community sample of 15 to 19-years-olds (N=46) in Waterloo, Canada. Two communicative perspective-taking tasks required participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 117 publications
1
23
1
Order By: Relevance
“…Although these variables have clearly different characteristics, it is generally considered that their respective overall values are equally good indicators of subjective well-being. However, the observed correlations have not been high enough to be able to state that they measure identical constructs (Banati and Diers, 2016;Casas, Baltatescu, Bertrán, González, and Hatos, 2013;Diener, et al 1999;Nilsen and Bacso, 2017). The scores obtained with the MWQ would indicate that somehow this new construct could form part of subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Although these variables have clearly different characteristics, it is generally considered that their respective overall values are equally good indicators of subjective well-being. However, the observed correlations have not been high enough to be able to state that they measure identical constructs (Banati and Diers, 2016;Casas, Baltatescu, Bertrán, González, and Hatos, 2013;Diener, et al 1999;Nilsen and Bacso, 2017). The scores obtained with the MWQ would indicate that somehow this new construct could form part of subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…WM refers to the ability to store and manipulate information, and it has been connected to perspective-taking and referential choice in at least two ways. Firstly, it underpins the storage and updating of the interlocutor's perspective and the comparison of that perspective with one's own to check for convergence (Nilsen & Bacso, 2017; Wardlow, 2013). Secondly, it may be implicated in the use of feedback in the case in which one of the interlocutors explicitly signals a mismatch between their perspective and that of their conversational partner.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nilsen and Graham () found that children with better inhibitory control were less egocentric in communicative perspective taking, yet they found no link between communicative perspective taking and working memory or cognitive flexibility. In contrast, Nilsen and Bacso () found that working memory strongly predicted adolescents’ communicative perspective taking (see Schuh et al, for similar findings).…”
mentioning
confidence: 96%